KEPENTINGAN JEPANG MELALUI JAPAN INTERNATIONAL COOPERATION AGENCY (JICA) DALAM PEMBANGUNAN MRT DI JAKARTA - Rifqi Muzakki Azwat; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The construction of the Mass Rapid Transit (MRT) in Jakarta has become an important infrastructure project for the Indonesian government. In this context, Japan has played an active role through the Japan International Cooperation Agency (JICA) as a partner in advancing the MRT project in the capital. The purpose of this study is to analyze Japan's interest through JICA in the construction of the MRT in Jakarta. In order to provide more specific accuracy to the results, the researcher uses the neorealism paradigm and the theory of foreign aid as a basic reference for research to clarify Japan's motives through JICA in the construction of the MRT in Jakarta. The analysis was carried out by analyzing books, officially published journals, documents, news. The results showed that Japan's motives in providing assistance to the Jakarta MRT project through JICA were divided into 3, namely humanitarian motives, economic motives, and socio-political motives. First, for humanitarian motives, where Japan uses this project to help people in partner countries in aspects of transportation technology as it is done to achieve JICA's fourth agenda. Second, for economic motives, in which Japan seeks to strengthen its economic influence and invest in long-term investment through foreign aid in the MRT project in Jakarta for Indonesia. Third, for socio-political motives, where the Japanese state as a driving force provides assistance with the aim of creating ties between the two countries, then Indonesia trusts Japan more in the aspect of security motives, for example, as in the Phase 2 MRT project because the technology is considered qualified and has security. good trains, and the existence of these motives also influences the Japanese economic motives which can carry out investment and import activities in Indonesia through this cooperation. Keywords: JICA, MRT, Foreign Aid